Artificial intelligence in business education: Benefits and tools - Camelia Surugiu; Cătălin Grădinaru; Marius-Răzvan Surugiu (Amfiteatru Economic, 2024)
Understanding the impact of artificial intelligence (AI) on education is vital for guiding teachers in developing educational tools. AI in education (AIEd) comes not only with opportunities but mostly with challenges for both educators and learners. Finding the proper tools to integrate AI into the learning framework represents a test for current and future generations. Even if most students acknowledged AI as a valuable tool, their interaction with AI in education seems more limited than expected. They mainly concentrated on few tools with higher awareness. This paper examines AI's support for educational activities, key drivers, and tools for business education. Survey data collected from 254 learners were analysed using multivariate binary logistic regression. Two research questions were formulated to verify if AI supports educational activities and what AI tools support business educational activities. Results show learners appreciate AI for aiding teachers in administrative tasks, personalising learning plans, and saving time. However, learners are unfamiliar with most benefits of AI tools, except computer vision, edge computing, and AI chatbots. The paper highlights the need to increase the use of AI in education to make students more familiar with AI tools and capitalise on them in business education.
Keywords: A23; I23; M15; O33; 330; artificial intelligence (AI); artificial intelligence in education (AIEd); instruments; benefits; Romania